Plastic residues and microplastics in agroecosystems: How Egyptian farmers perceive the risks? - Kassem, Hazem S.; Mosa, Ahmed; Bhattacharya, Mondira; AbouElnaga, Mohammed; Elagamy, Moshira; Atiya, Doaa; Elgamal, Belal; Osbahr, Henny (Frontiers in Sustainable Food Systems, 2025)
The widespread presence of microplastic contamination is now recognized as an evolving issue with detrimental effects on agroecosystems. In response, governments and environmental organizations have emphasized the severity of plastic residues and microplastics (MPs) to the public, urging responsible and sustainable plastic use. However, limited research has been conducted to investigate farmers’ perceptions of plastic pollution. This study aims to identify the various risks—environmental, economic, health, and social—associated with plastic residues and MPs in three governorates of Egypt. The study found that 48.3% of farmers exhibited a low level of awareness regarding microplastic contamination. Despite this, most farmers perceived MPs as a significant threat to the well-being of their communities. The accumulation of plastic residues has led to aesthetic pollution, identified as one of the most prominent social risks. Among environmental risks, air quality contamination was highly recognized. However, the impacts of MPs on soil and water contamination, agricultural productivity, and animal health remain areas where farmers lack a comprehensive understanding. The findings revealed that farmers’ levels of awareness were positively influenced by factors such as plasticulture size, the diversity of plasticulture systems, years of plasticulture utilization, and geographical location (specifically, the Giza governorate). Conversely, satisfaction with plastic quality had a significantly negative effect on farmers’ perceptions. These results highlight the urgent need for awareness programs and campaigns targeting farmers to educate them about the hazards associated with plastics and MPs. Additionally, policymakers and other stakeholders in the plastic value chain must collaborate to address and mitigate the problems caused by plastics and MPs in agriculture.